Association of cardiac ischemic score and coronary collateral circulation. - Arzu, J; Siddique, MA; Rahman, F; Anam, MK; Zaman, SM; Awal, A; Subedi, B; Fatema, K (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 275-279 The abstract of this article is available on the PubMed website